Analisis Item Instrumen Pengukur Kompetensi Berpikir Kritis Siswa Berbasis ESD di Sekolah Dasar - Syifa Novita Fauziyah; Ghullam Hamdu (Indonesian Journal of Social Science Education (IJSSE), 2021)
This research is a development instrument based on Education for Sustainable Development (ESD). This Studi aims to analyze and produce an instrument of critical thinking competence based on ESD students thai is valid, reliable, level of difficulty, and the level that corresponds to the item. The test of the instrument was multiplied by 75 students in high class at SDN 1 Jayaraga, Garut. The data collection instrument in this study was in the form of 15 multiple choice test question and 25 communicatioan questionnaires. The discussion during the research in the form of FGD (Forum Group Discussion). Then the two instruments are said to reliable as evidenced by Cronbach alpha value was 7 questions, the questionnaire was 13 statements tha were approved by the respondents. Then the analysis of the suitability level with the calculation of the logit and value on the MNSQ outfit is close to 1, the ZSTD outfit is close to 0, and the Pt Mean Corr is close to 0 that there is no instrument that needs to be changed or repaired.